Improving Syntax Learning Achievement throughLesson Study Based Learning on IV Semester Students of Indonesian Language and Letter Education Study Program Pakuan University - ., Suhendra; Chodijah, Siti (Journal of Humanities and Social Studies, 2018)
The aim of this research is to know the process of Lesson Study based learning and the improvement of sytaxis learning achievement through Lesson Study based learning on IV semester students of Indonesian Language and Letter Education Study Program Pakuan University. This research is desgined as action research with lesson study based. There are four cycles used in this research.  Every stage on lesson study cycles comprise of plan, do, see. The data colleted is analyzed using descriptive qualitative method. The result of the research shows that lesson study based learning process gives a wide opportunity, both to the lecturer and students to innovate, enhance activity, creativity, communication, and interaction during learning process. Collbaorative learning using various strategies, method, technique and media can focused the students in learning and understanding knowledge. It is relevant to be applied in syntactic learning where students discuss the events of concreat and contextual language use. Based on the observation result, the observers agree to the application of lesson study based learning. Students’ response are also positive towards the lesson study based learning, which can be stated that students are more interested in learning using lesson study based learning. Students’ syntax learning achievement  shows an improvement, average score for posttest in first cycles 68,78, average score insecond cycle is77,45, average score in third cycle is 78,15, and average score in fourth cycles is 80,52. Therefore it can be concluded that there is an improvement on syntaxis learning achievement through lesson study based learning on IV semester students of Indonesian Language and Letter Education Study Program Pakuan University.